Jamur Upas (Upasia salmonicolor) pada Daun Kopi di Pagilaran - Ambarwati Harsojo Tjokrosoedarmo (Universitas Gadjah Mada, 1996)
The result of this study showed that most of fungus as thin mycelial layer on the coffee leaves were connected with pink fungus on the branch. The microscopic study showed the hyaline mycelia producing perpendicular branches, and anastomose easily; the hyphal cells contain one to four nuclei. The anatomy of pink incrustation of fungus composed of four layers: 1. basal layer; 2. intermediate layer; 3. subhymenial layer; and 4. hymenial layer. From the results of both field and laboratory studies it is concluded that the fungus on the coffee leaf is actually the cobweb stage of pink fungus occurring on the leaves, and it is notorious fungus because it may act as inoculum source of pink disease.